Enduring undetectable MRD and updated outcomes in relapsed/refractory CLL after fixed-duration venetoclax-rituximab - Seymour, John F.; Kipps, Thomas J.; Eichhorst, Barbara F.; D'Rozario, James; Owen, Carolyn J.; Assouline, Sarit; Lamanna, Nicole; Robak, Tadeusz; de la Serna, Javier; Jaeger, Ulrich; Cartron, Guillaume; Montillo, Marco; et al. (Blood, 2022)
The MURANO trial (A Study to Evaluate the Benefit of Venetoclax Plus Rituximab Compared With Bendamustine Plus Rituximab in Participants With Relapsed or Refractory Chronic Lymphocytic Leukemia [CLL]; ClinicalTrials.gov identifier #NCT02005471) reported superior progression-free survival (PFS) and overall survival (OS) with venetoclax-rituximab (VenR) vs bendamustine-rituximab (BR) in relapsed/refractory (R/R) CLL. Patients were randomized to 2 years of VenR (n = 194; rituximab for the first 6 months) or 6 months of BR (n = 195). Although undetectable minimal residual disease (uMRD) was achieved more often with VenR, the long-term implications of uMRD with this fixed-duration, chemotherapy-free regimen have not been explored. We report MRD kinetics and updated outcomes with 5 years' follow-up. Survival benefits with VenR vs BR were sustained (median PFS [95% confidence interval]: 53.6 [48.4, 57.0] vs 17.0 [15.5, 21.7] months, respectively, P < .0001; 5-year OS [95% confidence interval]: 82.1% [76.4, 87.8] vs 62.2% [54.8, 69.6], P < .0001). VenR was superior to BR, regardless of cytogenetic category. VenR-treated patients with uMRD at end of treatment (EOT; n = 83) had superior OS vs those with high-MRD+ (n = 12): 3-year post-EOT survival rates were 95.3% vs 72.9% (P = .039). In those with uMRD at EOT, median time to MRD conversion was 19.4 months. Of 47 patients with documented MRD conversion, 19 developed progressive disease (PD); median time from conversion to PD was 25.2 months. A population-based logistic growth model indicated slower MRD median doubling time post-EOT with VenR (93 days) vs BR (53 days; P = 1.2 × 10−7). No new safety signals were identified. Sustained survival, uMRD benefits, and durable responses support 2-year fixed-duration VenR treatment in R/R CLL. •Two-year fixed-duration VenR offers sustained PFS, OS, and MRD benefits over BR in R/R CLL, regardless of presence of high-risk biomarkers.•Median MRD doubling time post-VenR EOT was 93 days, with 19 months from uMRD to MRD conversion and another 25 months from conversion to PD. [Display omitted]